PENGARUH MODEL PEMBELAJARAN GUIDED INQUIRY TERHADAP KETERAMPILAN BERPIKIR KREATIF SISWA PADA PEMBELAJARAN IPAS KELAS V SDN KEBOANANOM GEDANGAN SIDOARJO - Thomas Alfa Andri Prasetiyo; Prastyo, Danang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Rudimentary school understudies frequently battle with inventive considering, especially in communicating their thoughts and tackling issues autonomously. This confinement emerges due to immature cognitive capacities. To address this issue, the guided request learning demonstrate is actualized to make an intelligently learning environment that improves conceptual understanding. This ponder points to analyze the viability of the guided request show in progressing students' imaginative considering aptitudes in science learning, particularly on the subject of light properties in fifth-grade rudimentary school. A quantitative approach with a Quasi-Experimental plan, particularly a Posttest-Only Control Bunch Plan, was utilized. Course VA served as the test bunch that gotten guided inquiry-based instruction, whereas Course VC acted as the control bunch, proceeding with ordinary instructing strategies. Data was collected through a creative thinking posttest given after the treatment. The data analysis technique used in this research used the normality test, homogeneity test and T-Test. This research was processed using IBM SPSS 21 for Windows. The results of the hypothesis test using the t-test stated that the output results in the t-test for equality of means column showed a sig value. (2-tailed) is 0.098, because the sig value (2-tailed) is 0.98<0.05 or the significant value is smaller than 0.05. Ho is rejected, which means there is a difference. So it can be concluded that there is an influence of the guided inquiry learning model on the creative thinking skills of fifth grade students at SDN Keboan Anom Gedangan Sidoarjo.